ANALISIS FINANSIAL USAHA KERAJINAN KALIGRAFI KULIT KAMBING DI KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Shanti Emawati; Endang Siti Rahayu; Sutrisna Hadi Purnomo; Ayu Intan Sari; Endang Tri Rahayu; Winny Swastike (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The  research  was  conducted  to  determine  the  feasibility  of  financial  on SMEs  calligraphy  goat  leather  in  Sukoharjo  District.  Research  was  done  from January 6 to March 26, 2015 in located in  Sukoharjo District. Survey methods was done  to  collect  primary  data  from  respondents  and  secondary  data  from  related institution. Census method was applied to sellect respondents. Criteria used to analyze the feasibility of financial on  SMEs calligraphy goat leather  were consisted of Benefit Cost  Ratio  (BCR),  Net  Present  Value  (NPV),  Internal  Rate  of  Return  (IRR)  and Payback Period (PPC), based on 6 years investment and 12% annual discount factor. The  result  showed  that  based  on  NPV,  IRR,  BCR  and  payback  period  analysis,  the most feasible of respondents was achieved on scale of 3 with value of  NPV =  Rp. 434,852,752.00, IRR = 37.93%, BCR = 1.92,  followed by on scale of 2 with value of NPV = Rp. 76,481,554.00, IRR = 22.51%, BCR = 1.37 and on scale of 1 with value of NPV  =  Rp.  34,883,505.00,  IRR  =  20.41%  dan  BCR  =  1.28.  In  term  of  payback period, respondents who had SMEs calligraphy goat leather on scale of 3 were able to return the investment during  2.39  years while on scale of 2 and on scale of 1 were 3.72 and 3.79 years, respectively.